Clinical translation in the virtual liver network - Kuepfer, Lars; Kerb, Reinhold; Henney, Adriano M. (CPT: pharmacometrics & systems pharmacology, 2014)
The liver is the central detoxifying organ, continuously removing xenobiotics from the vascular system. Given its role in drug metabolism, a functional understanding of liver physiology is crucial to optimizing drug efficacy and patient safety. The Virtual Liver Network (VLN), a German national flagship research program, focuses on producing validated computer models of human liver physiology. These models are used to analyze patient-derived data and thereby gain mechanistic insights in the processes underlying drug pharmacokinetics (PK). CPT Pharmacometrics Syst. Pharmacol. (2014) 3, e127; doi:10.1038/psp.2014.25; published online 30 July 2014
Gesehen am 16.02.2021